Análisis de los componentes asociados al concepto de innovación pedagógica (2021)
This paper presents the results of a documentary analysis focused on the components associated with the concept of pedagogical innovation. Based on the axial coding proposal, it was possible to account for the problems associated with this concept, its conflictive relationship with information and communication technologies (ICTs), its actors, relationships with the institutional culture, the classes and the perspectives associated with its understanding. In the literature, there is a need to broaden the discussions around the role of ICTs in pedagogical innovation processes, as well as the prevailing need to reflect on the tensions generated within institutions due to institutional cultures. Thus, the participatory and multiscale character that pedagogical innovation acquires in its application in educational contexts is emphasized.